Effect of Seasonal Canopy Management on the Performance of Chenin blanc/99 Richter Grapevines - Volschenk, C.G.; Hunter, J.J. (South African Journal of Enology and Viticulture, 2017)
The effect of seasonal canopy management on the performance of a Chenin blanc/99Richter vineyard with excessive vegetative growth and trained onto a Lengthened Perold trellising system, was studied. No canopy management (shoots growing in all directions) resulted in over-exposure of the bunch zone directly above the cordon, whereas sunlight reflection from the soil was drastically reduced. In contrast, canopy management led to a much more balanced penetration of sunlight into the bunch zone - here, shoot positioning played a big role. Air flow through the canopy was highest when partial defoliation, in combination with suckering and shoot positioning, was applied; these practices had the highest impact on canopy microclimate and appearance. Canopy management reduced the incidence and severity of Botrytis/sour rot - shoot positioning in particular seemed critical. Highest yields were obtained by applying shoot positioning and defoliation or topping. Although suckering was labour intensive and reduced yields, it resulted in significant labour savings for critical time-dependent actions such as pruning and harvesting. Total grape quality and wine typical flavour were improved by seasonal canopy management.